Testing of unified power flow controller (UPFC) model in IEEE9 bus power system network using PSCAD/EMTDC and MATLAB software - Nur Azira, Mohd Saleh (2010)
Unified Power Flow Controller (UPFC) is the most widely used Flexible ac Transmission system ( FACTS ) device to control the power flow and to optimize the system stability in the transmission line. It should be installed to control the voltage, as well as to control the active and reactive power flow through the transmission line. This project is using PSCAD/EMTDC and MATLAB software to model and to verify the UPFC system in order to improve its performance in power system. MATPOWER in MATLAB software used to run the power flow of IEEE 9 bus power system network. Then, by using PSCAD/EMTDC software, IEEE 9 bus system was designed and the result of power flow 9 bus system using PSCAD/EMTDC was compared with the power flow in MATPOWER. The result of active power, P (MW) , reactive power ,Q (MVar) and power loss were compared to make sure that both software have the similar answer with only 1% difference. The power flow in both softwares must be similar before injecting the UPFC system. Then, the active power and reactive power performance will be improved due to injecting the UPFC device. Stability and transient performance of active and reactive power was analyzed